Ultrasound Evaluation of Lung Fields in Healthy Dogs: Scanning Technic and Aspects of Normality. - Modena, Diego Ferreira Alves; Unruh, Silvana Maria; Goldfeder, Guilherme Teixeira; Filho, José Henrique Hildebrand Grisi; Itikawa, Paula Hiromi; Larsson, Maria Helena Matiko Akao; Lorigados, Carla Aparecida Batista (Acta Scientiae Veterinariae, 2018)
Background: The ultrasound exam has always played a secondary role in pulmonary imaging, with its applicability restricted in emergency care to screen for pleural and/or pericardial effusion, pneumothorax and pulmonary contusion. The recognition of different reverberating artifacts arising from the normal aerated lungs (A lines) and in the presence of lungs with interstitial and/or alveolar infiltrates (B lines) led to wider application of the technique in patients with respiratory syndrome. The objective of this study was to describe the ultrasound imaging methodology and the aspects of the pleura, pleural space and lung fields in healthy dogs. Materials, Methods & Results: Twenty healthy dogs of different breeds and ages, males and females were evaluated in this study; good health status was confirmed by physical examination, electro and echocardiographic assessment, thoracic radiography and systemic arterial blood pressure measurements. Dogs were scanned by a single examiner experienced in diagnostic imaging and previously trained for 6 months in thoracic ultrasound image interpretation. A MyLab 40 with a microconvex multifrequency probe (5-8 MHz) was used in this study. Evaluation was performed in an orthopneic position (standing or sternal recumbecy) under manual containment. Ultrasound examinations were based on the VetBLUE (Veterinary Bedside Lung Ultrasound Exam) protocol. Lung fields were regionally scanned at the 2nd-3rd, 4-5th, 6-7th and 8-9th intercostal spaces in the right and left hemithorax. A subxiphoid window was added to screen for free fluid in the pleural space and/or pericardial sac. Pleural sliding and A lines, that are hyperechoic parallel equidistant lines arising from the visceral pleura-lung interface could be easily seen at all intercostal spaces in all dogs in this sample, with more difficult visualization at the 2nd-3rd intercostal space. B lines were observed in seven out of twenty dogs (35%). However, this artifact was limited to one intercostal space and a maximum of two lines were detected per field. B line artifacts were more commonly seen in the right hemithorax, at the level of the 8-9th intercostal space however without significant differences. In the subxiphoid window evaluation A lines were not detected. Discussion: The observation of B lines in healthy dogs was previously described and as in our study there were no significant differences relative to B line observation relatively to the intercostal space neither between the right and the left hemithorax. B lines are generally associated with decreased pulmonary aeration in response to interstitial/alveolar infiltration, which generates reflections and comet tail artifacts. The low number of B lines observed in this study may be associated with larger veins or lymphatics vessels, focal interstitial thickening or microatelectasia. The high respiratory frequency does not interfere in the sonographic evaluation. The dyspnea presented for animals with acute respiratory syndromes can be aggravated in stress situations, such as the displacement to the radiology service and manipulation necessary to the radiographic projections. Regional scanning by some acoustic windows allows rapid assessment of the thorax, with significant contributions to decision making in emergency situations. However, ultrasonography does not eliminate the need for other imaging modalities such as radiography and computed tomography and should be seen as a screening tool for patients presenting with acute respiratory syndromes.